A Colonized Dream: Fragmented Identity and Betrayal in Sunetra Gupta’s Memories of Rain - Liton Baron Sikder (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Sunetra Gupta’s debut novel, Memories of Rain, explores the complexities of cultural dislocation and the lingering effects of colonialism through Moni, a Bengali woman who migrates to England. This essay examines Moni’s struggle to forge an identity amidst conflicting emotions and a fractured sense of belonging. It analyzes how her romanticized view of England, shaped by English literature, collides with the harsh realities of life as an immigrant, ultimately leading to her disillusionment and return to Calcutta.  This article draws on critical scholarship to explore themes of “colonized otherness,” memory, nostalgia, and the search for a hyphenated identity. Moni’s journey reflects the challenges of navigating cultural clashes, betrayal, and the enduring power dynamics between colonizer and colonized. The analysis reveals how Gupta utilizes literary elements and the power of memory to portray Moni’s search for self-discovery and reclamation of her Bengali heritage.